Serum Zinc Levels as a Potential Predictive Marker for Hepatic Carcinoma: A Meta-Analysis - Bansal, Abhishek; Prashant , Praveen; Dixit, Pragya; Vashist , Sonia (New Visions in Medicine and Medical Science Vol. 1, 2024)
Introduction: Zinc, a crucial trace element in the human body, plays a pivotal role in various physiological processes due to its involvement in enzyme structure and function. Its significance in health and disease, particularly in liver disorders and cancer, has gained attention. However, inconsistencies exist in literature regarding zinc levels and their association with hepatic carcinomas. Methods: A meta-analysis was conducted following PRISMA guidelines to analyze the relationship between serum zinc levels and hepatic cancer. Data were extracted from epidemiological studies retrieved from NLM-PubMed databases. Inclusion criteria involved studies assessing blood zinc levels' association with liver cancer and providing mean values with standard deviation. Results: Seven eligible studies were included, showing significant heterogeneity. The combined average zinc level in hepatic carcinoma patients was 74.06 µg/dL (95% CI: 61.0 - 87.06), indicating a substantial deviation from normal levels. Publication bias was observed. Conclusion: The meta-analysis underscores the importance of zinc in liver cancer risk assessment and disease progression. Lower than expected pooled zinc levels in hepatic carcinoma patients highlight its potential as a predictive marker for liver malignancies and chronic liver diseases. Further research is warranted to elucidate zinc's precise role and clinical implications in hepatic carcinogenesis.